URGENSI FIQIH TARBAWI DALAM PERSPEKTIF MAQASHID SYARI’AH - Saifuddin Yuliar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
This paper examines a small part of substance of the problems. Therefore it is still embryotic and pioneer. However, this embryonic and pioneer effort is the key gatekeeper for the scientists in this aspect of this quite prospective fiqh tarbawi issue. For further study and freedom in order to increase the scientific treasures in this study then opened access to the gate study of fiqh tarbawi or education in a comprehensive. This paper answers the negative assumptions addressed to Islam with its educational system which seems strong, even considered primitive, can not be assumed as a form of disparaging or demeaning.